Porphyromonas Gingivalis - A Periodontal Pathogen with Potential Role in Rheumatoid Arthritis and its Association with Anti-CCP and Anti-MCV Antibodies Positivity - Selimov, Pavel; Firkova, Elena; Damjanovska Krstikj, LJubinka; Delcheva, Ginka; Stankova, Teodora; Stefanova, Katya; Maneva, Ana; Batalov, Anastas (Synergy Publishers, 2022)
Background: In recent studies, a strong association between rheumatoid arthritis (RA) and chronic periodontal disease (CPD) has been identified, indicating common disease pathogenesis and risk factors. One of them is the presence of the pathogen Porphyromonas gingivalis (PG), which can initiate the process of citrullination, by secreting the enzyme Porphyromonas Peptydil Arginine Deminase (PPAD). The aim of the study is to show the presence of PG in RA patients, and to evaluate the association of the PG presence with anti-citrullinated proteins/peptides (ACPA) positivity i.e. anti CCP and anti MCV positivity. Methods: The study included 80 participants - 30 patients which fulfilled 2010 ACR/EULAR RA classification criteria and 50 controls, which were genetically analyzed for the presence of PG by Chelex®100 method and polymerase chain reaction (PCR) and for the presence of anti CCP and anti MCV autoantibodies with the ELISA method. Results: Twenty out of thirty RA patients (80 %) and 16 out of 50 controls (32%) were positive for PG. (χ 2 = 11.461, p <0.001 for OA and χ2 = 13.91, p <0.001 for HC). Of the PG-positive RA patients, 83% had positive anti-CCP and 79% had positive anti-MCV test. The odds ratios OR of 25 and 19 were statistically significant (p = 0.008 and p =0,014 respectfully). Conclusions: PG was present more frequently in RA patients and there was a statistically significant association with anti CCP and anti MCV antibodies.
Keywords: Rheumatoid arthritis; Chronic periodontal disease; Porphyromonas gingivalis; ACPA; anti-CCP antibodies; anti-MCV antibodies